Effect of Diabetes Condition on Topical Treatment of Binahong Leaf Fraction in Wound Healing Process - Kintoko Kintoko; Hanifah Karimatulhajj; Trie Yuni Elfasyari; Ersi Arviana Ihsan; Teguh Adiyas Putra; Puspawan Hariadi; Citra Ariani; Nurkhasanah Nurkhasanah (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Diabetes mellitus (DM) is a metabolic disease which is becoming the first number of health problem in Indonesia, based on the results of the Basic Health Research of Ministry of Health in 2013. One of the diabetes complications affected by high levels of blood glucose is diabetic ulcers wich 85% the number of cases was overed by amputation as the result of improper handling. Herbal treatments could be an alternative treatment of diabetic ulcers, one of them is binahong plant. The results of previous studies have shown the ability of ethanolic extract of binahong leaf in accelerating wound healing in diabetic rats. This study would be a continued study to test five kinds of binahong leaf fractions (FDB) with gradual solvent polarity in accelerating wound healing in diabetic ulcer. Wound healing parameters observed were percentage of wound healing from the wound diameter contraction. The test begins with ethanolic extract of binahong leaf fractionation to produce fractions of hexane (FHDB), chloroform (FKDB), ethyl acetate (FEADB), and ethanol (FEDB). Water fraction (FADB) was obtained from ethanolic leaf extract residues of binahong leaf extraction. Each fraction activity was tested topically twice daily on dorsal of test animals that created wounds using a punch biopsy 5 mm diameters. Grouping of test animals were divided into 13 groups with normal control group (non diabetes), negative control (diabetes + topical application of biocream®), positive control (diabetes + topical application of madecassol), and 10 diabetes groups with topical application of 5 kinds of binahong leaf fractions with each fractions consist of a concentrations of 5% and 10% with biocream® as a vehicle. Diabetic parameters measured include blood glucose levels (KGD) and weight lost percentage (PB%) in day 1 and 10 during a 10-day treatment. The results showed the influence of KGD in the condition of diabetes on wound healing rats diabetic ulcers which topically treated with binahong leaf fractions. FADB 10% has significant differences potention in wound healing process in diabetic rats macroscopically that accelerates wound contraction compared with negative and positive control groups (p<0,05).